On the fallacy of using orthogenetic models of rectilinear change in arvicolid teeth for estimating the age of the first human settlements in Western Europe. (17th August 2016) - Palmqvist, Paul; Duval, Mathieu; Diéguez, Antonio; Ros-Montoya, Sergio; Espigares, Ma. Patrocinio
Abstract : Lozano-Fernández et al. (Lozano-Fernández I, Blain HA, López-García JM, Agustí J. 2014. Biochronology of the first hominid remains in Europe using the vole Mimomys savini: Fuente Nueva 3 and Barranco León D, Guadix-Baza Basin, south-eastern Spain. Hist Biol: Int J Paleobiol. doi:10.1080/08912963.2014.920015) recently published age estimates for two Late Villafranchian sites of Orce (Guadix-Baza basin, SE Spain), BL-D and FN-3, which provide some of the earliest evidence of human presence in Western Europe. The estimates were obtained from mean Lm1 values of the water vole Mimomys savini preserved in the sites and a couple of rectilinear equations derived in the Atapuerca TD section for site age on tooth length. However, this chronometric tool has problems that discourage its use in biostratigraphy, including: (1) the assumption of an orthogenetic trend of Lm1 increase during the evolution of the M. savini/Arvicola lineage; (2) the use of a chronology for the TD section not supported by original ESR data; (3) the discrepancies between the mean Lm1 values published for the TD levels and (4) the chronological ranges predicted when the standard deviations are used, which are exceedingly large as to be of value for biostratigraphic purposes. As a result, the pseudo numerical ages estimated for the Orce sites only add noise to the timing of the first human dispersal in Europe, which is based on a combination of results from well-established techniques such as palaeomagnetism, biostratigraphy and ESR.